Baitul Maal wat Tamwil (BMT) Digital Transformation Strategy in Accelerating MSME Empowerment: A Systematic Literature Review (2019-2025) - Fatoni, Sulton; Bakir, Ach; Dharodjah, Ulya (Jurnal Ilmiah Ekonomi Islam, 2026)
This research aims to synthesize and map the strategy for empowering Micro, Small, and Medium Enterprises (MSMEs) through Islamic microfinance institutions, especially Baitul Maal wat Tamwil (BMT), in the midst of the massive acceleration of the digital economy. The main focus of this study is to analyze how digital transformation can answer the challenges of capital accessibility, financial inclusion, and service efficiency for micro business actors. Using the Systematic Literature Review (SLR) method through the PRISMA protocol, this study synthesized 35 key articles filtered from reputable databases (Scopus, Crossref, and Google Scholar) in the publication time range of 2019 to 2026. The results of the study show that the main key to the success of MSME empowerment lies in three integrative pillars: (1) the adoption of Financial Technology (fintech) in sharia operations to expand the range of services, (2) the digitization of Islamic philanthropic instruments (ZISWAF) as sustainable productive capital, and (3) digital literacy improvement programs for business actors. The research findings confirm that the digital synchronization of the functions of Maal and Tamwil is able to accelerate the achievement of economic independence in line with the principles of Maqashid Sharia. However, structural challenges such as cybersecurity risks, regulatory inequality, and low digital literacy of human resources remain critical obstacles. This research provides managerial implications in the form of a strategic roadmap for Islamic microfinance managers to standardize technology to create an inclusive, transparent, and sustainable microfinance ecosystem in the industrial era 5.0.